A harmonized and standardized in vitro approach produces reliable results on silver nanoparticles toxicity in different cell lines. Issue 12 (12th May 2021) - Andreoli, Cristina; Prota, Valentina; De Angelis, Isabella; Facchini, Emiliano; Zijno, Andrea; Meccia, Ettore; Barletta, Bianca; Butteroni, Cinzia; Corinti, Silvia; Chatgilialoglu, Chryssostomos; Krokidis, Marios G.; Masi, Annalisa; et al.
Abstract: Despite the widespread use of silver nanoparticles (AgNPs) in different fields and the amount of investigations available, to date, there are many contradictory results on their potential toxicity. In the present study, extensively characterized 20‐nm AgNPs were investigated using optimized protocols and standardized methods to test several toxicological endpoints in different cell lines. The agglomeration/aggregation state of AgNPs in culture media was measured by dynamic light scattering (DLS). DNA and chromosomal damage on BEAS‐2B and RAW 264.7 cells were evaluated by comet and micronucleus assays, while oxidative DNA damage by modified comet assay and 8‐oxodG/8‐oxodA detection. We also investigated immunotoxicity and immunomodulation by cytokine release and NO production in RAW 264.7 and MH‐S cells, with or without lipopolysaccharide (LPS) stimulus. Transmission electron microscope (TEM) analysis was used to analyze cellular uptake of AgNPs. Our results indicate different values of AgNPs hydrodynamic diameter depending on the medium, some genotoxic effect just on BEAS‐2B and no or slight effects on function of RAW 264.7 and MH‐S in absence or presence of LPS stimulus. This study highlights the relevance of using optimized protocols and multiple endpoints to analyze the potential toxicity of AgNPs and to obtain reliable and comparable results. Abstract : In this study, optimized protocols and standardized methods were used for evaluating the potential in vitro toxicity of extensively characterized 20‐nm silver nanoparticles (AgNPs). AgNPs dispersions, characterized in culture media, were tested for cytotoxicological, genotoxicological, and immunotoxicological effects on cell lines representative of different route of exposure. Cellular uptake was also investigated. This study highlights the relevance of using optimized protocols and multiple endpoints to investigate the potential toxicity of AgNPs in order to obtain reliable and comparable results.